A time-dependent expression for modulus of subgrade reaction of saturated cohesive foundation soils - Shukla S.K. (My University, 2025)
This paper presents an analytical derivation of a time-dependent expression for the modulus of subgrade reaction of the saturated cohesive foundation soil considering the primary consolidation aspect. The newly developed expression involves parameters that can be determined by conducting one-dimensional laboratory consolidation test on the undisturbed soil specimens. An experimental verification of the analytical expression is presented to observe its accuracy. A parametric study is also presented to point out the care required while selecting the parameters used in the expression. J. Ross Publishing, Inc. © 2008